Water source transformation in a semi-arid inland basin: Insights from an isotope-based integrated framework - Jin Sun; Yixuan Wang; Tingxi Liu; Guixin Zhang; Limin Duan; Shaojie Chu; Bo Zhang; Yajun Zhou; Yixuan Zhang; Ting Liu (Journal of Hydrology: Regional Studies)
Study region: The Xilin River Basin, a typical grassland-type inland basin in a semi-arid inland area of northern China. Study focus: To quantify the dynamic transformations among groundwater, river water, and precipitation at the basin scale, we integrated a fixed-covariate MixSIAR isotope mixing model, a structural equation model (SEM), and hydrogeological structural analysis. This integrated framework allowed us to systematically characterize the spatiotemporal transformation patterns and their driving mechanisms among the three water sources. New hydrological insights for the region: Both δ2H and δ18O values of precipitation and river water showed clear seasonal enrichment during the rainy season and depletion during the non-rainy season, with shallow groundwater exhibiting stronger seasonal isotopic responses than deeper groundwater. Model selection results identified “Section & Date” as the optimal fixed covariates for groundwater and river-water mixtures, while “Date” alone was optimal for precipitation. Under these optimal configurations, upper-reach river water during the rainy season was primarily recharged by groundwater (82.84 %) and precipitation (17.16 %), while in the non-rainy season, river water (80.88 %) and groundwater (19.12 %) in the lower basin were recycled to the atmosphere via evapotranspiration and contributed to local precipitation. SEM analysis revealed that meteorological factors (precipitation and temperature) and hydrological factors (runoff and groundwater level) were the dominant drivers of isotope dynamics and source partitioning, whereas ecological variables had relatively limited influence.